Meristik Ikan Gabus - Zega, Hude Venial (CV. SINAR HOWUHOWU, 2025)
This study aimed to analyze the meristic characteristics of snakehead fish (Channa striata) collected from freshwater ecosystems in Gunungsitoli, North Sumatra Province. The research was conducted from November 2025 to January 2026 using five specimens of snakehead fish as samples. A descriptive quantitative method was applied in this study. The observed meristic characters included the number of dorsal, pectoral, pelvic, anal, and caudal fin rays, as well as the number of lateral line scales, transverse body scales, and scales around the caudal peduncle. Observations were carried out directly in the laboratory using optical instruments to ensure accuracy. The results indicated that the meristic characteristics of Channa striata from Gunungsitoli waters were relatively uniform among individuals, although slight variations were observed in some characters. These variations were still within the normal range and consistent with previously reported descriptions of the species. The relative uniformity of meristic characters suggests that the environmental conditions of the study area support normal growth and development of snakehead fish. The findings of this study are expected to serve as baseline data for fisheries biology studies, resource management, and further research on the population structure of snakehead fish.